509 Child restraint system use in Mexico. What does the law say?. (1st September 2016) - Hidalgo-Solórzano, Elisa; Gómez-García, Lourdes; Pérez-Núñez, Ricardo; Lunnen, Jeffrey C; Hyder, Adnan
Abstract : Background: During 2013, the mortality rate for Road Traffic Injuries (RTI) in Mexico was 13.4 per 100, 000 habitants, about 1.8% of all deaths were children amongst children from 0–5 years of age as a result of a RTI while travelling as car occupants. Our objective is to analyse the current legislation regarding the use of Child Restraint Systems (CRS) and to estimate its prevalence in three Mexican cities. Methods: We performed a review of the existing Mexican legislation on CRS use; focused on six variables: age, weight and height of children, location inside the vehicle, use of restraints or car seat and anchorage system. As well, as a cross-sectional study conducted in 3 Mexican cities to determine the prevalence of CRS use. Two rounds of observation were performed in preschools, between August and December of 2014. We observed all vehicles that stopped in front of, or up to 5 metres away from the preschool's entrance to drop off children, we recorded information of the children, the vehicle, drivers and occupants. Results: In total, 68 traffic regulations were analysed in order to describe the Mexican legislation on children occupants of motor vehicles of 4 or more wheels. The most important finding was that the mandatory use of CRS is not defined in any of the reviewed regulations, however there is an agreement that children should travel in the rear seats. We observed a total of 3, 019 motor vehicles and 3, 508 children estimated to be 5 years of age or less. The prevalence of CRS use in both rounds was 16.24% (95% CI: 15.04, 17.51); 14.69% (95% CI: 13.05, 16.44) in round one and 17.76% (95% CI: 16.01, 19.61) in round two. Conclusions: In Mexico, since 2003 was established CRS use, and location of children in the rear seat, as a health policy applicable throughout the country. Twelve years later, is necessary for governments of the states and local authorities implement national health policies, to strengthen strategies of the Decade of Action for Road Safety.